FEATURES OF PROVISION OF SUSTAINABLE NAVIGATION AIDS FUNCTIONING UNDER HELIOGEOPHYSIC DISTURBANCES - Kalashnyk-Rybalko, Myroslava (Proceedings of National Aviation University (archive), 2018)
Purpose: The aim of this study is to research features of navigation provision of civil aviation aircraft using satellite navigation systems under heligeophysic disturbances. Methods: The analysis of requirements for civil aviation aircraft navigation support in terms of implementing the concept of ICAO CNS / ATM using as the primary means of global navigation satellite systems and organization of space weather data provision for air traffic. The analysis of the main ways for modeling the values of total electron content of the Earth ionosphere. The analysis of problems of navigation support of civil aviation aircraft while using satellite navigation systems in terms of quiet and disturbed space weather. Development of a generalized complex model of satellite navigation systems functioning under the influence of external destabilizing factors. Results: А generalized complex model of satellite navigation systems functioning under the influence of external destabilizing factors was developed. There were proposed the main mechanisms of functional stability of aircraft navigation aids operation in terms of heligeophysic disturbances distructive impact on them. Discussion: Exploring of the possibility of taking into account ionospheric parameters variations under space weather heligeophysic disturbances and clarifying the correction of satellite navigation system ionospheric errors based on the analysis of sygnal parameters of navigational sygnals that passed by the ionosphere in order to ensure the steady functioning of navigation aids under heligeophysic disturbances.